MASALAH PENAMBANGAN PASIR YANG TIDAK DILAPORKAN KEPADA DINAS PERTAMBANGAN DAN ENERGI ( DISTAMBEN ) DI KEC KOTA BANGUN KAB KUTAI KARTANEGARA - Redy Ready (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
abstractThe mining business must meet the procedures and requirements that have been determined by the government of Kutai regency to obtain the mining license, but what happened in the district of Kota Bangun there are many problems such as sand mining is illegal by society and pernambang sand official at findings excavated material new that zircon sand that can be used to make the ceramic, refractory bricks, printing, metal and acrospace material which is certainly much more useful and more expensive, but it does not report activityit to the Department of Mines and Energy (Distamben) local not only that, the negative impact caused by sand mining illegal is the environmental damage that resulted in peeling overburden cause damage top soil, and water systems that are the bottom of the river so that the volume of water increases because not restrained by vartikel sand to settle to the bottom of the river is the concrete result of the floods, as well as air pollution and noise generated from the diesel engine vacuum sand that does not pay attention to the operating distance of residential areas.